Vegetarian diets during pregnancy: effects on the mother's health. A systematic review. Issue 2 (11th December 2020) - Baroni, Luciana; Rizzo, Gianluca; Goggi, Silvia; Giampieri, Francesca; Battino, Maurizio
Abstract : While interest in vegetarian nutrition has been steadily increasing, some aspects have not yet been consistently investigated. Abstract : While interest in vegetarian nutrition has been steadily increasing, some aspects have not yet been consistently investigated. One topic requiring evidence-based confirmation is the adoption of a vegetarian diet during pregnancy and lactation. Maternal diet is not only correlated with the fetus's and infant's health, but appears relevant for that of the mother as well. Not only is an adequate delivery of nutrients to the fetus and infant mandatory, but the increased physiological needs of the maternal body require an adequate supply of nutrients and can represent harmful stress events that may lead to well-defined pathological conditions. In this review, we aim to systematically investigate state-of-the-art of vegetarian diets during pregnancy and lactation, focusing on maternal nutritional status and pregnancy outcomes. Data are scarce, often inconsistent and not homogeneous for many of the topics we considered, mainly because only a few studies have been performed in developed countries, whereas other studies have derived from developing countries, where vegetarianism can be a proxy indicator of malnutrition. For this reason, we did not find sufficient data to provide evidence-based information and recommendations. To date, the available literature does not clearly support a negative impact on the mother's health and pregnancy outcomes, but, analogously with the findings in the vegetarian adult population, an improvement in the quality of studies might facilitate finding more information on the possible positive impact of well-planned vegetarian diets during pregnancy and lactation. More epidemiological and interventional studies are warranted, in order to address the question as to whether vegetarian nutrition represents an advantage for the mother or poses nutritional issues that need further attention.